FLOUTING MAXIM ANALYSIS ON BBC RADIO 1 YOUTUBE CHANNEL â€œKIDS ASK RYAN REYNOLDSâ€ - Damiri, Adenan; Fiskaryanti, Aida; Nainggolan, Billi Andara; Amalia, Nidia (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study discusses the analysis of the flouting maxim using a YouTube video on the BBC Radio 1 YouTube channel "Kids ask Ryan Reynolds". The purpose of this study is to describe the flouting maxim and describe the function of the flouting maxim in a conversation in the video. Maxim is a part of pragmatics. The researchers get the data by analyzing the conversation or an interview in a YouTube video on the BBC Radio 1 YouTube channel "Kids ask Ryan Reynolds". The researchers used Grice's theory called the cooperative principle with four types of maxims: maxims of quantity, maxims of quality, maxims of relevance, and maxims of means. In this analysis using a conversation on the BBC Radio 1 YouTube video "Kids ask Ryan Reynolds", there are 8 data, 8 of which follow the maxim of relevance, and 1 data follow the maxim of quality. From each data, researchers could discover multiple flouted maxims in the conversation, up to 3 flouted maxims in each one. The consistently followed maxim in the video is the maxim of relevance because, throughout the video, Ryan always responds with a relevant topic. On the other hand, the most common and most consistently flouted maxim by Ryan Reynolds in the video is the maxim of manner.